Mobile Taskflow in Context: A Screen Shot Study of Smartphone Usage - Karlson, Amy; Iqbal, Shamsi; Meyers, Brian; Ramos, Gonzalo; Lee, Kathy; Tang, John (Proceedings of CHI 2010, 2010)
The impact of interruptions on workflow and productivity has been extensively studied in the PC domain, but while fragmented user attention is recognized as an inherent aspect of mobile phone usage, little formal evidence exists of its effect on mobile productivity. Using a survey and a screenshot-based diary study we investigated the types of barriers people face when performing tasks on their mobile phones, the ways they follow up with such suspended tasks, and how frustrating the experience of task disruption is for mobile users. From 386 situated samples provided by 12 iPhone and 12 Pocket PC users, we distill a classification of barriers to the completion of mobile tasks. Our data suggest that moving to a PC to complete a phone task is common, yet not inherently problematic, depending on the task. Finally, we relate our findings to prior design guidelines for desktop workflow, and discuss how the guidelines can be extended to mitigate disruptions to mobile taskflow.